2020
DOI: 10.18203/2320-1770.ijrcog20202731
|View full text |Cite
|
Sign up to set email alerts
|

A study of prevalence of thyroid dysfunction in abnormal uterine bleeding

Abstract: Background: Abnormal uterine bleeding (AUB) is one of the most frequent presentation to gynecology OPD. AUB is a common but complicated clinical presentation and occurs in 15-20% of women between menarche to menopause and significantly affects the women’s health. Thyroid disorders are more common in women than in men and cause abnormal sexual development, menstrual irregularity, infertility and premature menopause. Objective of this study was to estimate the prevalence of thyroid disorders in women in reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the present study, thyroid dysfunction was prevalent in 35% patients who presented with AUB, out of which 27% patients had hypothyroidism which was the most common thyroid dysfunction and 8% patients had hyperthyroidism, whereas 65% patients were euthyroid. In a study conducted by Rai et al 17 thyroid dysfunction was seen in 24.9% patients, out of which 14.4% patients had subclinical hypothyroidism, 9.2% patients had overt hypothyroidism, 1.3% patients had hyperthyroidism and 75.2% patients were euthyroid. Similar findings were seen in several other studies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present study, thyroid dysfunction was prevalent in 35% patients who presented with AUB, out of which 27% patients had hypothyroidism which was the most common thyroid dysfunction and 8% patients had hyperthyroidism, whereas 65% patients were euthyroid. In a study conducted by Rai et al 17 thyroid dysfunction was seen in 24.9% patients, out of which 14.4% patients had subclinical hypothyroidism, 9.2% patients had overt hypothyroidism, 1.3% patients had hyperthyroidism and 75.2% patients were euthyroid. Similar findings were seen in several other studies.…”
Section: Discussionmentioning
confidence: 92%
“…This is similar to the study done by Narula et al 15 and Pahwa et al 16 who observed 32.8% and 42% cases respectively in the age group 31-40 years. Rai et al 17 and Subedi et al 11 also observed that AUB was more common in the age group of 31-40 years.…”
Section: Discussionmentioning
confidence: 92%